Comprehensive evaluation on water resource carrying capacity based on DPESBR framework: A case study in Guiyang, southwest China. (20th September 2020) - Peng, Tao; Deng, Hongwei
Abstract: Water resource is the crucial strategy resource for sustaining development, and is also a fundamental basis resource for building ecological environment, especially in karst areas of southwest China. In this study, the DPESBR conceptual model was first proposed and used to conduct sustainability evaluation on regional water resources in Guiyang. Based on the DPESBR model, 42 indicators were chosed and empowered by adopting combination weight. Results showed that the pressure on local water resources increased with soaring of total population and proportion of domestic water used by urban and rural residents. Countermeasures and options adopted by the local population had reduced the amount of agricultural irrigation water consumption and industrial water use ratio during the production course of regional agriculture and industry, but the increased water use scale had brought about a growth in resource depletion. Moreover, the sustained development of water resource system in the area was on the decline because of joint impacts of water contamination and use. Humanity could achieve the sustaining utilization of water resources in the region and the sustained progress of compound system by making adjustments on medium and short time bucket factors such as cultural heritages, value concepts, economical framework and technical makeup.